Contribution to the Development of Nano-Composite Materials Based on ZnO and Polymethyl Methacrylate Structural and Optical Study - Abdellah Elkaiem; Omar Boukraa (Iraqi Journal of Physics)
In this study,  thin films of pure and aluminum (Al)-doped zinc oxide/polymethyl methacrylate (ZnO/PMMA) with two different amounts (5% and 7%) using the sol-gel and spin coating methods were created and then heated at two temperatures (450 and 750°C). Many characteristics were used to analyze the resulting samples, including X-ray diffraction (XRD), UV-visible, and infrared (IR) absorption spectroscopy. The X-ray diffraction analysis of the samples indicated that they formed a hexagonal structure of ZnO known as wurtzite, with a preferred direction labelled as (101). UV-visible analysis of the specimens' optical characteristics has helped calculate the gap energy using the Tauc method. The energy value is 4.12 eV. The optical characteristics of the samples were analyzed by the Fourier Transform Infrared (FTIR), which shows the presence of absorption peaks attributed to the existence of the new phase that cannot be observed through the X-rays, which is a phase of spinel zinc aluminate  (ZnAl2O4).